Circuits, systems and signals for bioengineers a MATLAB-based introduction - Semmlow, John L. (Academic Press series in biomedical engineering.)
This book guides the reader through the electrical engineering principles that can be applied to biological systems and are important to biomedical studies. The basic engineering concepts that uderlie biomedical systems, medical devices, biocontrol, and biosignal analysis are explained in detail. Circuits, Signals and Systems for Bioengineers is the perfect textbook for the one-semester bioengineering course usually offered in conjunction with a laboratory on signals and measurements which presents the fundamentals of systems and signal analysis. The target course occupies a pivotal position i.